Developing BrightHearts: A Pediatric Biofeedback‐Mediated Relaxation App to Manage Procedural Pain and Anxiety. - Morrow, Angela M.; Burton, Karen L. O.; Watanabe, Melissa M.; Cloyd, Benjamin H.; Khut, George P. (Pain Practice, 2018)
Abstract: Objective: The objective of this study was to develop a child‐friendly biofeedback‐mediated relaxation device called BrightHearts. Methods: Qualitative data were collected at a tertiary pediatric hospital to inform an iterative design process. Clinicians participated in expert group interviews to identify practical considerations that would facilitate the use of BrightHearts during procedures and provide feedback on prototype designs. Children 7 to 18 years of age participated in interactive exhibitions of the prototypes and were interviewed about their experiences using BrightHearts. Results: Twenty‐four clinicians participated in 6 group interviews. Thirty‐nine children participated in interactive exhibitions, and 21 were interviewed. Clinicians placed high value on the following factors in the management of procedural pain: providing children with an element of control, the use of relaxation techniques, and the use of portable electronic devices such as iPads. They highlighted the need for BrightHearts to be cost effective, portable, and capable of engaging children's interest. They confirmed the utility of developing a biofeedback‐assisted relaxation device for children. Based on the factors identified by clinicians, BrightHearts was developed as an iPad application (app) paired with a wireless heart rate monitor. The BrightHearts heart rate biofeedback app displays digital geometric artwork that responds to changes in heart rate. Children 7 to 17 years of age understood the concept of biofeedback and operated the app by slowing their heart rates. Conclusion: The BrightHearts app can be used to teach children biofeedback‐assisted relaxation. Ongoing studies are evaluating its efficacy for the management of procedural pain in children.